OPTIMASI KEUNTUNGAN PADA HOME INDUSTRY ARYADY BAKERY MENGGUNAKAN LINEAR PROGRAMMING - Rangga R. Mandalika; James U.L. Mangobi; Marvel G. Maukar (Discovery : Jurnal Ilmu Pengetahuan, 2022)
Home industry Aryady Bakery produces three types of bread, namely brown bread, cheese chocolate bread, and moca bread, but the profits are not maximized. In addition, the process of purchasing raw materials for making bread is carried out with estimates without definite calculations. Based on this, a production model is given in the form of linear programming to optimize profits in the Aryady Bakery Home industry. After observing and collecting data, the decision variables from this linear programming problem are obtained, namely the amount of brown bread, cheese and moca to be produced. In addition, the constraint functions for the model are obtained, namely raw materials, electricity, working hours of production machines, and labor hours, and the coefficients of the function variables on the objective function using the advantages of one brown bread, chocolate cheese bread, and moca bread. Furthermore, the profit optimization calculation process uses a linear program with a simple method with the help of LINDO and TORA software. The maximum yield obtained by producing as many as 4260 brown bread, 1200 cheese chocolate bread, and 500 moca bread each month is Rp. 3,600,460. Keywords: Linear programming, Simpleks, Profit Optimization